The Role of Opportunity Recognition in Linking Digital Entrepreneurial Literacy and Entrepreneurial Intention - Nurhayani Nurhayani; Agung Muliaman Anas; Andi Anggi Kemalasari; Muhammad Akbar; Nurfadilah Sindika Sari (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2025)
This study examines the effect of digital entrepreneurial literacy on entrepreneurial intention through opportunity recognition among university students. The study is motivated by the growing importance of digital competencies in supporting entrepreneurial activities in the digital economy. This study applies a quantitative approach using a structured questionnaire distributed to 84 university students selected through purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling with the assistance of SmartPLS software. The results show that digital entrepreneurial literacy does not have a significant direct effect on entrepreneurial intention. However, digital entrepreneurial literacy has a positive and significant effect on opportunity recognition, and opportunity recognition has a positive and significant effect on entrepreneurial intention. The findings also confirm that opportunity recognition fully mediates the relationship between digital entrepreneurial literacy and entrepreneurial intention. This study highlights opportunity recognition as a key mechanism through which digital entrepreneurial literacy contributes to entrepreneurial intention. The findings imply that entrepreneurship education should not only develop students’ digital entrepreneurial competencies but also strengthen their ability to identify and evaluate business opportunities.